The effects of local ischemic preconditioning and topical hypothermia in renal ischemia/reperfusion injury in rats - Ribeiro,Guilherme Behrend (2017)
Abstract Purpose: Topical hypothermia and local ischemic preconditioning have been shown to reduce renal ischemia-reperfusion (I/R) injury individually. We examined whether combination of both strategies lessens renal I/R injury. Methods: Post right nephrectomy, 40 male Wistar rats were randomly assigned to five experimental protocols performed in the left kidney: topical hypothermia without ischemia (TH), warm ischemia (IR), ischemic preconditioning followed by warm ischemia (IPC+IR), cold ischemia (TH+IR), and ischemic preconditioning followed by cold ischemia (IPC+TH+IR). Eight randomly assigned right kidneys constituted the control group. After 240 min of reperfusion, the left kidney was retrieved to evaluate histological changes, lipid peroxidation and antioxidant enzymes activity. Serum was collected to evaluate urea and creatinine. Results: IPC+TH+IR group revealed no difference to any other group subjected to ischemia in relation to histological changes, lipid peroxidation and antioxidant enzymes activity. Creatinine was lower in IPC+TH+IR group compared with IPC+IR, but showed no difference compared to TH+IR group. Conclusions: Combination of local ischemic preconditioning (IPC) and topical hypothermia conferred no protection in renal I/R injury. Moreover, local IPC solely followed by warm ischemia impaired renal function more than warm ischemia alone.